PENGARUH KINERJA LINGKUNGAN, PENGUNGKAPAN LINGKUNGAN, PERPUTARAN KAS, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS - Eva Mustika; Aprilia Whetyningtyas; Dianing Ratna Wijayani (Jurnal Ekonomi Bisnis dan Akuntansi, 2021)
This study aims to examine the effect of environmental performance, environmental disclosure, cash turnover, and inventory turnover on profitability. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019. The sampling method of this study used purposive sampling which resulted in 99 samples. The data analysis technique used is panel data regression. The results of this study are environmental performance has a positive effect on profitability, while environmental disclosure, cash turnover, and inventory turnover has no effect on profitability.